Midterm elections 2010 - Impact of electorate expectations on midterm - Kratochvíl, Jakub; Dvořáková, Vladimíra, 1957-; Šubrta, Václav; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2011)
This thesis focuses on analysis of the importance of electorate expectations for voter behavior in mid-term elections. We will modify the traditional Alesina-Rosenthal model to include electorate expectations. Using this new model, we will show that Obama's loss in the 2010 mid-term elections was caused by high electorate expectations which were created during the campaign for Presidency in 2008. With the help of our framework, we will demonstrate that electorate expectations played a crucial role in several historical mid-term elections.
Vedoucí práce: Vladimíra Dvořáková
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2011
Rok obhajoby 2011
Keywords: mezinárodní a evropská studia - diplomacie [obor dipl. práce]; diplomové práce; master's theses